Author Correction: An Endophytic Bacterial Consortium modulates multiple strategies to improve Arsenic Phytoremediation Efficacy in Solanum nigrum. Issue 1 (December 2018) - Mukherjee, Gairik; Saha, Chinmay; Naskar, Nabanita; Mukherjee, Abhishek; Mukherjee, Arghya; Lahiri, Susanta; Majumder, Arun; Seal, Anindita
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.